(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This paper provides a comprehensive examination of the noun as one of the fundamental components of English grammar. The study investigates both the structural and semantic dimensions of nouns, emphasizing how form and meaning interact to shape syntactical behavior. Structurally, the paper discusses simple, derivative, and compound nouns, outlining the morphological principles that determine their formation. Semantically, it analyses major noun categories, including concrete and abstract nouns, animate and inanimate nouns, proper and common nouns, as well as countable and uncountable types, demonstrating how these classifications reflect the conceptual organization of the world in language. Furthermore, the article explores the syntactical functions of nouns in various sentence models, focusing on their roles as subjects, direct and indirect objects, complements, objects of prepositions, and adverbial modifiers. Special attention is given to how structural complexity and semantic distinctions influence the distribution of nouns within sentence patterns